The Public’s’ Perception of Corporate Social Responsibility (CSR) and Its Impact on Marketing Strategies - Frigerio, Claudia (The IIE, 2017)
The utilisation of Corporate Social Responsibility (CSR) as a means of enhancing an organisation’s brand image and reputation has seen an increase in popularity. Stakeholders often favour and possess a positive perception of organisations who incorporate CSR into their business practice. Generally, the public perceive CSR as a means for organisations to address the impact that they possess on the environment surrounding them. Thus, the proposed study developed out of a necessity to determine the public’s overall perception of CSR and whether it has an impact on marketing strategies. It is assumed that, although there is public scepticism, the utilisation of CSR practices would generate a positive perception of an organisation and in turn, increased brand reputation. The research uses a qualitative approach and collects data through the use of in-depth semi-structured interviews with the general South African public. The results of the research provided insight into the public’s subjective understanding of CSR and how the utilisation of CSR as a marketing strategy may be advanced. Overall, findings illustrated that the public does possess a positive perception of CSR and that CSR may in fact be utilised as a marketing tool.
Keywords: Corporate social responsibility; Brand image; Brand reputation; Public perception; Marketing strategy